Cobra and Cayman forage grass hybrids pass National performance trial in Tanzania. A milestone towards registration - Mwendia, Solomon; Nzogela, Beatus; Karimi, Peggy; Peters, Michael (2024)
Evaluation and registration of new crop varieties is a global practice. In Tanzania, the Tanzania Official Seed Certification Institute (TOSCI) guides this process. In 2023, the Alliance of Biodiversity International and CIAT (ABC) in collaboration with the Tanzania Livestock Research Institute (TALIRI) visited the TOSCI with the aim of discussing the possibilities of registration of elite forage hybrids which had been worked on by the two institutes especially in the Southern highlands namely, Brachiaria (syn Urochloa) hybrid species (Cayman and Cobra) from Alliance of Bioversity & CIAT. Registration allows uptake for the lines by the private sector to increase availability and access of the registered seeds at the last mile. Equally, it smoothens import or export of seeds in a country